Anti‐leukemic and anti‐angiogenic effects of d‐Limonene on K562‐implanted C57BL/6 mice and the chick chorioallantoic membrane model. Issue 4 (21st November 2018) - Shah, Bhavini B.; Baksi, Ruma; Chaudagar, Kiranj K.; Nivsarkar, Manish; Mehta, Anita A.
Abstract: Background: d ‐Limonene, a monoterpene from citrus fruit has been found to have chemopreventive and chemotherapeutic activities in various types of cancers. In this study, we evaluated the in vivo effect ofd ‐Limonene on a K562‐induced model of chronic myeloid leukemia (CML) in C57BL/6 mice. Method: The tail vein injection model of K562 cells in immunocompromised C57BL/6 mice was developed and evaluated for characteristics of the disease. The mice were treated withd ‐Limonene and evaluated for haematological parameters. We also evaluated the effect ofd ‐Limonene on angiogenesis using the chick chorioallantoic membrane (CAM) assay. Results: In a complete blood count, a significant dose‐dependent reduction in white blood cell, neutrophil and lymphocyte counts, but an elevation in red blood cell count and haemoglobin content was observed withd ‐Limonene treatment compared to the disease control or untreated group. In the CAM assay, d ‐Limonene produced a significant dose‐dependent reduction in number of blood vessels in treatment groups compared to the vehicle‐treated group. Conclusion: These studies suggest promising anti‐leukemic and anti‐angiogenic effects ofd ‐Limonene in the treatment of CML.